2021
DOI: 10.3390/cancers13246210
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for Prediction of Immunotherapy Efficacy in Non-Small Cell Lung Cancer from Simple Clinical and Biological Data

Abstract: Background: Immune checkpoint inhibitors (ICIs) are now a therapeutic standard in advanced non-small cell lung cancer (NSCLC), but strong predictive markers for ICIs efficacy are still lacking. We evaluated machine learning models built on simple clinical and biological data to individually predict response to ICIs. Methods: Patients with metastatic NSCLC who received ICI in second line or later were included. We collected clinical and hematological data and studied the association of this data with disease co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Nevertheless, keeping in mind the objective to ultimately support decision making and patient stratification, a minimal (11 features), near-optimal, set of BSL variables was selected and denoted mBSL. It was defined as the first seven variables reaching the plateau (CRP, heart rate, neutrophils to lymphocytes ratio, neutrophils, lymphocytes to leukocytes ratio, liver metastases and ECOG score), complemented with four variables with established prognostic or predictive value and available in routine care: PD-L1 expression (50% cut-off) 3 , hemoglobin 30 , SLD 22 and LDH 31,32 . Applying stringent criteria to the RNAseq data (see methods), we selected 167 transcripts as candidates for final variable selection using Bolasso regression model to identify the optimal set of predictors 33 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, keeping in mind the objective to ultimately support decision making and patient stratification, a minimal (11 features), near-optimal, set of BSL variables was selected and denoted mBSL. It was defined as the first seven variables reaching the plateau (CRP, heart rate, neutrophils to lymphocytes ratio, neutrophils, lymphocytes to leukocytes ratio, liver metastases and ECOG score), complemented with four variables with established prognostic or predictive value and available in routine care: PD-L1 expression (50% cut-off) 3 , hemoglobin 30 , SLD 22 and LDH 31,32 . Applying stringent criteria to the RNAseq data (see methods), we selected 167 transcripts as candidates for final variable selection using Bolasso regression model to identify the optimal set of predictors 33 .…”
Section: Resultsmentioning
confidence: 99%
“…Baseline tumor mutational burden showed similar predictive value initially (AUC = 0.646) 11 , but led to disappointing results in a recent prospective study 46 and others found it to be more prognostic than predictive 47 . Baseline blood counts were previously reported to predict overall survival 44,[48][49][50] and treatment response (AUC = 0.74) 43 . The ROPRO score, derived from a large pan-cancer cohort and incorporating baseline clinical and biological data (27 variables) achieved a c-index of 0.69 and a 3-months AUC of 0.743 for prediction of survival in the OAK clinical trial 51 .…”
Section: Application To Clinical Trial Outcome Prediction From Early ...mentioning
confidence: 99%
“…Multiple studies in bladder cancer have indicated that patients with an Eastern Cooperative Oncology Group (ECOG) performance status (PS) of 2 have worse outcomes with ICI therapy than those with ECOG PS < 2 [34][35][36]. Prospective clinical trials with ECOG PS ≥ 2 are lacking, despite ICI therapy being an enticing option for the poor PS population.…”
Section: Discussionmentioning
confidence: 99%
“…For this, machine learning is another promising approach. Benzekry et al developed machine learning models by collecting clinical and hematological data and predicted the disease control rate of ICIs at the individual level [ 146 ]. Alternatively, instead of a simple combination of biomarkers, recent developments in high-throughput analyses such as next-generation sequencing and mass spectrometry may make it easier to identify a panel of biomarkers.…”
Section: Discussionmentioning
confidence: 99%